Beta-alanine supplementation enhances judo-related performance in highly-trained athletes - Kratz, Caroline de Andrade; Painelli, Vitor de Salles; Andrade Nemezio, Kleiner Marcio de; Silva, Rafael Pires da; Franchini, Emerson; Zagatto, Alessandro Moura [UNESP]; Gualano, Bruno; Artioli, Guilherme Giannini (Elsevier B.V., 2017)
Objectives: In official judo competitions, athletes usually engage in 5-7 matches in the same day, performing numerous high-intensity efforts interspersed by short recovery intervals. Thus, glycolytic demand in judo is high and acidosis may limit performance. Carnosine is a relevant intracellular acid buffer whose content is increased with beta-alanine supplementation. Thus, we hypothesized that beta-alanine supplementation could attenuate acidosis and improve judo performance. Design: Twenty-three highly-trained judo athletes were randomly assigned to receive either beta-alanine -(6.4 g day(-1)) or placebo (dextrose, same dosage) for 4 weeks. Methods: Performance was assessed before (PRE) and after (POST) supplementation through a 5-min simulated fight (randori) followed by 3 bouts of the Special Judo Fitness Test (SJFT). Blood samples were collected for blood pH, bicarbonate (HCO3-) and lactate determination. Results: Beta-alanine supplementation improved the number of throws per set and the total number of throws (both p < 0.05). Placebo did not change these variables (both p > 0.05). Blood pH and HCO(3)(-)reduced after exercise (all p < 0.001), with no between-group differences (all p > 0.05). However, the lactate response to exercise increased in the beta-alanine group as compared to placebo (p < 0.05). Conclusions: In conclusion, 4 weeks of beta-alanine supplementation effectively enhance judo-related performance in highly-trained athletes. (C) 2016 Sports Medicine Australia. Published by Elsevier Ltd. All rights reserved.
Keywords: Carnosine; Buffers; Athletes; Dietary supplement